An In vitro Evaluation of Antimicrobial Efficacy of new Nano-zinc Oxide Eugenol (NZOE) - Mina Zarei; Maryam Javidi; Maryam Gharechahi; Maryam Joybari; Parastoo Tajzadeh; Mohsen Arefnejad (Mashhad University of Medical Sciences, 2018)
Introduction: This interventional in-vitro study aimed to evaluate the antimicrobial activity of a new Nano Zinc OxideEugenol (NZOE) sealer in comparison with AH26 and Pulpdent common root canal sealers against endodontic pathogens. Methods: The antimicrobial efficacy of three sealers(NZOE, AH26 and Pulpdent)  against Enterococcus faecalis (ATCC 29212), Escherichia coli (ATCC 25922), Streptococcus mutans (ATCC700610), Candida albicans (ATCC 90028), and Staphylococcus aureus (ATCC 25923)  were evaluated by Direct Contact Test (DCT) at five  different time intervals 0, 2, 14, 48 hours and 7 days. The results were statistically analyzed using SPSS software and Kruskal-Wallis at 5% significance level. Results: All three tested sealers had antimicrobial activity against microorganisms involved in this study. Fresh NZOE sealer eliminated all microorganisms tested, except the strain of E. faecalis colony which was reached to zero after 2 hours. However, AH26 and Pulpdent failed to completely kill all of the E. faecalis colony during the entire observation period. Also, NZOE showed a significant antimicrobial action (P